Prevalence of comorbid major depressive disorder in Type 2 diabetes: a meta‐analysis of comparative and epidemiological studies. Issue 8 (1st July 2019) - Wang, F.; Wang, S.; Zong, Q.‐Q.; Zhang, Q.; Ng, C. H.; Ungvari, G. S.; Xiang, Y.‐T.
Abstract: Aims: To examine the average point prevalence of major depressive disorder in people with Type 2 diabetes and its associated factors in a comprehensive meta‐analysis. Methods: Two researchers independently conducted a systematic literature search of PubMed, EMBASE, PsycINFO and Cochrane databases. Studies reporting the prevalence of major depressive disorder in people with Type 2 diabetes were identified and analysed using a random‐effects model. Results: A total of 26 studies meeting the inclusion criteria were included in the study. The point prevalence of major depressive disorder was 14.5% (95% CI 7.9–25.3; I ²=99.65). People with Type 2 diabetes were more likely to have major depressive disorder compared with the general population (odds ratio 1.73, 95% CI 1.38–2.16). Subgroup and meta‐regression analyses showed that study site, study type, diagnostic criteria and age significantly moderated the prevalence of major depressive disorder. Conclusions: In this meta‐analysis, the average point prevalence of major depressive disorder in people with Type 2 diabetes was high. Routine screening and more effective interventions should be implemented for this population. What's new?: This was the first meta‐analysis to examine the prevalence of major depressive disorder in people with Type 2 diabetes in studies using standardized diagnostic instruments. People with Type 2 diabetes were more likely to have major depressive disorder compared with the general population. Routine screening and more effective treatments and interventions should be implemented for people with Type 2 diabetes and major depressive disorder.